Determinants of interest rate differentials for selected countries - Er, Hong Teck (2008)
Five macroeconomic variables are tested and analyzed for their impact on the real interest rate differentials of Australia, Canada, Germany, Japan and Singapore relative to the United States. It finds that governments have scope for conducting appropriate macroeconomic policies that affect the real interest rate differentials vis-à-vis the United States.